2004
DOI: 10.1111/j.1423-0410.2004.00528.x
|View full text |Cite
|
Sign up to set email alerts
|

The serological and genetic basis of the cis‐AB blood group in Korea

Abstract: Sixty cis-AB01 donors were identified. cis-AB01/O01 or O02 were the most common genotypes (36/60) detected only in A(2)B(3) donors, and cis-AB01/B101 (nine of 60) was the least common genotype identified only in A(2)B donors. Surprisingly cis-AB01/A102 (15/60) was identified in a variety of phenotypes (A(1)B(3), A(1)B(x) or el, A(int)B(3)).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 7 publications
1
52
0
Order By: Relevance
“…The allele frequencies of O, A, and B were 50.1, 29.5, and 20.4 %, respectively, in controls and 49.4, 32.0, and 18.5 %, respectively, in GC patients. These results were consistent with previous studies [19]. As compared with blood group O, blood group A, but not groups AB or B, was associated with a significantly increased risk of GC overall (adjusted OR 1.28 and 95 % CI 1.09-1.50).…”
Section: General Characteristics Of Subjectssupporting
confidence: 92%
See 1 more Smart Citation
“…The allele frequencies of O, A, and B were 50.1, 29.5, and 20.4 %, respectively, in controls and 49.4, 32.0, and 18.5 %, respectively, in GC patients. These results were consistent with previous studies [19]. As compared with blood group O, blood group A, but not groups AB or B, was associated with a significantly increased risk of GC overall (adjusted OR 1.28 and 95 % CI 1.09-1.50).…”
Section: General Characteristics Of Subjectssupporting
confidence: 92%
“…Thus, there is the possibility of a discrepancy between serological phenotypes and those predicted from genotypes. However, the error rate is considered to be negligible because the ABO subgroup frequency in the general population of southwestern Korea included in this study, (Yeonggwang and Muan counties and Namwon city) was only 0.114 % [19]. It was also reported that the discordance rates between genotypes and phenotypes defined as groups A, B, AB, and O were 0.18 % (2/1134 samples) in a Japanese population and 0.12 % (2/ 1700) in our previous study [17,20].…”
Section: Discussionmentioning
confidence: 86%
“…Song et al genotyped 222 samples and reported the ABO genotype frequencies of A101/A101, A101/O02, and A101/ B101 to be 0.00%, 1.35%, and 0.45%, respectively [15]. Also, the cis-AB blood group is rare and the overall frequency of this blood group was determined to be 0.0354% among southwestern Korean blood donors [16].…”
Section: Discussionmentioning
confidence: 99%
“…Cases of interest were tested by both automated devices. In cases of the AB blood type, forward typing with anti-A1 (anti-A1 lectin, Ortho Clinical Diagnostics) was additionally performed to confirm A 2 B or A 2 B 3 phenotypes, which are typical cis-AB blood phenotypes in Korea [8][9][10]. Reagents used in serologic tests were as follows: forward typing was performed using Anti-A, Anti-B, and Anti-D BioClone reagent (Ortho Clinical Diagnostics) by both tile and tube method.…”
Section: Evaluation Of Suspected Cis-ab Casesmentioning
confidence: 99%